Reações de 1,1,1-tricloro-4-metoxi-3-penten-2-ona com hidrazinas monosubstituídas - Silva, Sidnei Moura e (2005)
The 1,1,1-trichloro-4-methoxy-3-penten-2-ona (CCl3COCH=CHOMe) reaction with hydrazines series (RNHNH2, where R = H, Me, tert-Bu, Ph, Ph(F)5, Ph-4-NO2, CO2Me e CONH2) yield to the pyrazoles N-substituted and derivatives formation by [3 + 2] ciclocondensations reactions. These compounds formation is regioespecific, it means, termodinamically controled (exception R = Me, tert-Bu). Concerning the presented conditions, we have found some cases where it was possible to isolate the 4,5-diidropirazois derivates (R = H, Ph, Ph(F)5, Ph-4-NO2, CO2Me e CONH2). In relation to some reaction conditions, it was also possible to obtain the pyrazoles in a one-pot conduction (R = H, Ph, e Ph-4-NO2) or through the intermediary 4,5-diidropyrazoles (R = C6F5 e CO2Me) dehydration. In one of the cases (R = CONH2), it was not possible to obtain the aromatization with the CONH2 permanency for the respective pyrazole formation through the dehydration with 96% sulfuric acid, due to the loss of carboxiamide group by hydrolyze during the reaction curse. This study has also presented the possibility of regioespecific obtaining in 5-carboxietilpyrazoles one-pot through the 1,1,1-tricloro-4-metoxi-3-penten-2-ona and hydrazine ciclocondensation followed by the trichloromethyl group (R = tert-Bu, Ph-4-NO2) hydrolyze. After that, it was tested some synthetic conditions for obtaining these 5-carboxietilpyrazoles in a regioespecific form, through the triclorometil group hydrolyze, which is directly linked to the (R = H, Ph, Me) pyrazoles by the simple ethanol addition. The experimental dadas, associated to the AM1 Molecular Orbital (MO) theorical calculation, shows that there is a relation between the substituent chemical effect and the formation regioespecific of these cycles, as well as the 4,5-dihydropyrazoles dehydration and in the trichlorometyl transformation attached in pyrazoles.